The antecedents and consequences of successful localization - Law, Kenneth S; Song, Lynda Jiwen; Wong, Chi-Sum; Chen, Donghua (Journal of International Business Studies, 2009)
Localization in the corporate setting is the extent to which expatriate managers are replaced by local employees originally held by expatriate managers. We sampled 229 multinational enterprises (MNEs) in the People's Republic of China and investigated the antecedents of localization success based on resource dependency theory. We developed a 40-item scale to measure human resource (HR) practices determined to contribute to successful localization. We also identified parent company support and top management's commitment as two sets of factors that predicted localization success. It was the first study that found a significant relationship between localization success and top management ratings of company performance.